Modulating the Gut Microbiota with Alginate Oligosaccharides In Vitro - Grégoire Bouillon; Olav Gåserød; Łukasz Krych; Josué L. Castro-Mejía; Witold Kot; Markku T. Saarinen; Arthur C. Ouwehand; Dennis S. Nielsen; Fergal P. Rattray (Nutraceuticals, 2022)
Alginate oligosaccharides (AOS) are non-digestible carbohydrates from brown kelp. As such, they are dietary fibers and may have prebiotic potential. Therefore, we investigated the capacity of gut bacteria to utilize AOS with single-strain cultures and as a complex bacterial community. Bifidobacterium adolescentis, Lacticaseibacillus casei and Lacticaseibacillus paracasei showed weak growth (relative to unsupplemented medium; p < 0.05) in the presence of AOS and alginate, while strong growth (p < 0.01) was observed for Bacteroides ovatus when grown with alginate as carbohydrate source. Enterococcus faecium and Enterococcus hirae were for the first time reported to be able to grow on AOS. Further, AOS as substrate was investigated in a complex bacterial community with colonic fermentations in an in vitro gut model. The in vitro gut model indicated that AOS increased short-chain fatty acid (SCFA) levels in donors with a low endogenous SCFA production, but not to the same level as inulin. Bacteroides was found to dominate the bacteria community after in vitro gut simulation with alginate as substrate. Further, stimulation of Bacteroides was observed with AOS in the gut model for two out of three donors with the third donor being more resistant to change. Our results allowed the identification of AOS utilizers among common gut species. The results also demonstrated the capacity of AOS to elevate SCFA levels and positively modulate the gut microbiota during in vitro simulated colon fermentations, although some subjects appear to be resilient to perturbation via substrate changes.